Dieta e uso de habitats por mamíferos carnívoros em mosaico formado por remanescentes de floresta atlântica e plantios florestais - Czarnobai, Simone (2012)
Understanding the coexistence of sympatric carnivores in disturbed environments requires knowing the way these predators share food resources. In this study, we investigated the diet of nine carnivore species that occur in a mosaic composed of Atlantic forest remnants and forest plantations in southern Brazil. Between 2006 and 2008 1038 fecal samples were collected along five 6 km transects that were established to sample the habitat diversity of the study area. The relatively high percentage (49.5%) of fecal samples identified to species level is due to a modification of the proposed methodology for the separation of guardhairs, as described herein. Mammalian prey was predominant on the diet of all carnivores studied, followed by birds. The food categories "reptiles", "fish", "vegetable" (fruits and seeds) and "invertebrates" were consumed occasionally. Niche breadth showed that felids are specialists in mammals and diet overlap was almost complete among this family. Nevertheless, such results could change if food categories were identified to lower taxonomic levels